EFEK TEKNIK THINK PAIR SHARE TERHADAP PEMAHAMAN MEMBACA TEKS NARATIF SISWA TAHUN KEDUA DI SMAN 1 KATEMAN, KABUPATEN INHIL - Andani, Siska; Aruan, Rumiri; ', Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This is a pre-experimental research with one group pre-test and post-test design. It aimed to find out a significant effect of Think Pair Share technique on reading comprehension in narrative texts of the second year students at SMAN 1 Kateman, INHIL Regency. The population of this research was all of the second year students at SMAN 1 Kateman which consists of 278 students. Cluster random sampling technique was used to select one class to be the sample. As a result, class XI Science 1 with 33 students was chosen as the sample. The instrument used was a reading test that consists of 35 questions in the form of multiple choice tests. The obtained data were analyzed by using SPSS version 16.0 for Windows. The results of data showed that mean score in post test was higher than mean score in pre test (79.42> 67.33). Then, the data analysis also showed that tobs was higher than ttable (2.72<15.194>2.03) in sig. 5% and 1%. It means that the alternative hypothesis was accepted and the null hypothesis was rejected. In other words, there is significant effect of Think Pair Share technique on reading comprehension in narrative texts of the second year students at SMAN 1 Kateman, INHIL Regency.